2019
DOI: 10.3390/ma12030494
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Assessment of Criticality Safety Constraints for Swiss Spent Nuclear Fuel Loading in Disposal Canisters

Abstract: This paper presents preliminary criticality safety assessments performed by the Paul Scherrer Institute (PSI) in cooperation with the Swiss National Cooperative for the Disposal of Radioactive Waste (Nagra) for spent nuclear fuel disposal canisters loaded with Swiss Pressurized Water Reactor (PWR) UO2 spent fuel assemblies. The burnup credit application is examined with respect to both existing concepts: taking into account actinides only and taking into account actinides plus fission products. The criticality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…It must however be noted that the USL used in real licensing applications will usually be refined in order to take into account burnup (see, e.g., Ref. [6]) as well as uncertainties and/or biases due to the employed methods, data as well as SFMS/UNF structures, geometries and materials.…”
Section: Context Of Optimization Assumptions and Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…It must however be noted that the USL used in real licensing applications will usually be refined in order to take into account burnup (see, e.g., Ref. [6]) as well as uncertainties and/or biases due to the employed methods, data as well as SFMS/UNF structures, geometries and materials.…”
Section: Context Of Optimization Assumptions and Strategymentioning
confidence: 99%
“…To achieve this, an optimization of the canister loadings will therefore be needed, and the scope of this paper is to present a methodology that could broaden the options for such optimization. More specifically, for a given initial population of UNF assemblies, the present optimization will aim at finding loading combinations that allow using the exact number of canisters required to dispose of all the available UNF population, while ensuring strict compliance with the two selected safety and design related constraints, namely the neutron multiplication (''k eff '') and the thermal heat output (or ''decay heat'') [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This limitation is adequate given the lack of knowledge on the underlying nuclear data distributions. Details on the NUSS methodology, its validation and application studies can be found in [9], [10], [11], [12], [13].…”
Section: Nuss: Nuclear Data Stochastic Sampling With Ace Filesmentioning
confidence: 99%
“…Figure taken from ref. [3]  The criticality safety model of the final disposal canister filled with fresh PWR (UO 2 ) fuel assemblies was implemented with the MCNP Monte Carlo framework [4].…”
Section: Preliminary Analysis For Pwr Fuelmentioning
confidence: 99%
“…Figure taken from ref. [3]  Canister loadings based on a determined loading curve can ensure a subcritical system.…”
Section: Preliminary Analysis For Pwr Fuelmentioning
confidence: 99%